Seasonal abundance of Chrysomya megacephala and C. albiceps (Diptera: Calliphoridae) in urban areas - PIRES, EVALDO M.; CARRARO, VINÍCIUS M.; ZANUNCIO, JOSÉ C. (Revista Colombiana de Entomología, 2008)
A faunistic analysis of sinantropic calliphorids, Chrysomya megacephala and C. albiceps, was carried out in the urban area of Volta Redonda city, Rio de Janeiro, Brazil from October 2000 to September 2001. Two traps baited with fresh sardine were used. A total of 4,101 specimens of the genus Chrysomya were collected. The highest abundance of adults occurred between December 2000 and January 2001. Chrysomya megacephala was the most abundant species (57.71%) reaching its highest number in December 2000, followed by C. albiceps (41.94%) with a population peak in January 2001. Chrysomya putoria was also present in some traps but only 14 individuals were collected. Correlations between the presence of these species and the weather variables indicated that the presence of C. megacephala was influenced by rainfall and temperature, while C. albiceps was only affected by rainfall.